Comparison between Pilates exercise and combination with transcen-dental meditation towards short-term memory among adult females - Az Zahra, Almira Fadhila; Supatmo, Yuswo; Ekaputera, Muhammad Reza Wijoko (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: Pilates is a kind of exercise that incorporates both physical and mental components in its practice. Transcendental meditation comprises a collection of approaches that center on attention and awareness cultivation. Upon reaching adulthood, a person must possess a significant level of cognitive ability to guarantee optimal production. Pilates and transcendental meditation have emerged as potential options for enhancing cognitive processes, especially short-term memory. Objective: This study aims to investigate the impact of Pilates exercise, both alone and in conjunction with transcendental meditation, on short-term memory. Methods: The present study used an experimental design including three parallel groups and performed a pre-test and post-test design. The participants in this study consisted of 45 adult females ranging in age from 25 to 55 years. They were selected using the purposive sampling method and were divided into three groups based on the interventions received. The first group received a combination of Pilates exercise and transcendental meditation (n=15), the second group received Pilates exercise alone (n=15), and the third group served as the control group (n=15). Both intervention groups participated in 16 sessions, which were performed three times per week over six weeks. The Scenery Picture Memory Test (SPMT) was used to assess short-term memory. The data analyses were done using the paired t-test and One-way ANOVA. Results: Significant improvements (p<0.05) in SPMT scores were found across all groups after their respective therapies. There were stark differences in the results of the SPMT between the group engaged in Pilates exercise and the group practicing transcendental meditation (p=0.001), as well as between the Pilates exercise group and the control group (p<0.001). Besides, a significant result was found between the Pilates exercise group and the control group (p=0.01). Conclusion: The Pilates exercise, whether performed alone or in conjunction with transcendental meditation, has been shown to enhance short-term memory. Notably, engaging in Pilates exercise with transcendental meditation has a more pronounced and efficacious outcome.